Predictors of prolonged length of hospital stay for infants with bronchiolitis (2018)
Among inpatients suffering from bronchiolitis, approximately a quarter may undergo a prolonged length of stay (LOS) for the treatment of their respiratory condition. However, there have been few research studies that have evaluated variables that may be associated with a prolonged LOS in these patients, especially in low-income and middle-income countries, where the clinical and economic burden of the disease is the greatest. In an analytical single-center cross-sectional study, we included a population of patients with acute bronchiolitis hospitalized between March and June 2016. We collected demographic and clinical information and the LOS of each patient. Prolonged LOS for bronchiolitis was defined as at least one hospital stay of 5 or more days. A total of 303 patients were included, with 176 (58.1%) male and a median (IQR) age of 3.0 (1.0-7.0) months. After controlling for gender, history of bronchopulmonary dysplasia, number of days with respiratory symptoms, the presence of apnea as an initial manifestation of bronchiolitis, and other underlying disease conditions, we found that the independent predictors of prolonged LOS for bronchiolitis in our study population included age (OR 0.92; 95% CI 0.84 to 0.99; p=0.049), history of prematurity (OR 6.34; 95% CI 1.10 to 36.46; p=0.038), respiratory syncytial virus isolation (OR 1.92; 95% CI 1.02 to 3.73; p=0.048), and initial oxygen saturation (OR 0.94; 95% CI 0.88 to 0.98; p=0.048). The factors identified should be taken into account when planning policies to reduce the duration of hospital stay in infants with bronchiolitis.